2016
DOI: 10.3906/zoo-1510-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary selenium nanoparticles on physiological andbiochemical aspects of juvenile Tor putitora

Abstract: A 70-day feeding trial was conducted to evaluate the effects of dietary supplementation of selenium nanoparticles (Se-NPs) on physiological and biochemical aspects of juvenile mahseer (Tor putitora) fish. Maintaining a 40% protein level, 2 different experimental diets supplemented with 0% Se-NPs and 0.68 Se-NPs mg kg -1 were fed to triplicate groups of fish. The experiment was conducted in a semistatic condition consisting of 6 fiber tanks. The fish were first acclimatized, and then 30 fish per tank were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 55 publications
2
96
0
2
Order By: Relevance
“…Selenium nanoparticles have been studied in fish and showed positive influence on its health after supplementation (Jamil, ; Khan et al, ; Zhang et al, ; Zhou, Wang, Gu, & Li, ). In the present study, increase in myeloperoxidase and respiratory burst activity was observed in the fishes exposed to nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium nanoparticles have been studied in fish and showed positive influence on its health after supplementation (Jamil, ; Khan et al, ; Zhang et al, ; Zhou, Wang, Gu, & Li, ). In the present study, increase in myeloperoxidase and respiratory burst activity was observed in the fishes exposed to nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lysozyme activity, haemolysis and haemagglutination activities also increased gradually with the feeding duration. The lysozyme activity is necessary for the upkeep of innate immune status of fish (Khan et al, ; Kumar, Garg, & Mudgal, ). Goldfish ( Carassius auratus ) when treated with a sufficient selenium showed higher plasma lysozyme activity (Choi et al, ), and similarly, dietary selenium supplementation in juvenile olive flounder ( Paralichthys olivaceus ) on the lysozyme activity found to be improved by Lee, Kim, Park, and Bai () and in yellowtail kingfish ( Seriola lalandi ) by Le and Fotedar () which are in line with the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium when available in sufficient amount is an essential trace element which has been proven to improve the growth performance, immune competence, antioxidative status and resistance against stressors (Khan et al, ; Küçükbay et al, ; Le & Fotedar, ; Liu, Wang, Ai, Mai, & Zhang, ). It has been demonstrated that requirements for Se can be high due to the low availability of Se from diets containing fishmeal and the effects of different physical and environmental stressors (Rider et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Se deficiency has been reported to result in a variety of diseases in animals, such as white muscle disease in lambs (Whanger, ), exudative diathesis in chicks (Thompson & Scott, ) and retained placentas in dairy cattle (Julien, Conrad, & Moxon, ). In fish, dietary Se deficiency has been demonstrated to cause the elevated mortality (Poston, Combs, & Leibovitz, ), depressed growth and feed efficiency (Lin & Shiau, ), increased oxidative stress (Bell, Cowey, Adron, & Pirie, ) and haemolytic rates (Khan et al., ). Thus, optimal dietary Se level is crucial for animal health.…”
Section: Introductionmentioning
confidence: 99%